A community-based participatory approach to delivering the Dealing with Dementia program to Black caregivers - Alexander, Karah; Epps, Fayron; Thornton, Jacque; Chester, Mia; Miles, Toni (Frontiers in Public Health, 2025)
BackgroundAlter is a community-based program created to address gaps in dementia awareness and caregiving support/resources for Black and faith communities. The Rosalynn Carter Institute for Caregivers (RCI) collaborated with Alter to adapt the existing Dealing with Dementia (DWD) program [DWDAlter] to better reach and meet the needs of Black families through relevant dementia education and practical caregiving strategies.ContextFaith-based partnerships were identified as a trusted place to start to deliver the pilot DWDAlter Program. Four focus groups were conducted with Black faith leaders, their congregants who identified as caregivers, and other community members to inform the adaptation of the program. RCI’s original agency-based DWD model was modified using the principles of Community-Based Participatory Research.Programmatic elementsInput from the focus groups shaped the DWDAlter protocol, which included: (a) facilitator “toolkit,” (b) program assessments, (c) procedure manual, and (d) a community recruitment plan. To test the pilot DWDAlter, 22 Black community members were trained as facilitators, including 10 (45%) from rural Georgia communities. Between June and August 2024, 15 facilitators conducted 27 DWDAlter sessions using these new materials. Outcomes of this pilot initiative include an assessment of participant demographics and program satisfaction (acceptability). Two hundred and sixty-four persons attended the sessions, 95% of whom identified as Black or African American. Seventy-nine percent were family caregivers for individuals living with dementia, and 83% strongly agreed that the program met their caregiving needs. Evaluation of program effectiveness, specifically changes in caregiving self-efficacy and dementia knowledge before and after participation, will be conducted at a later time.DiscussionWhile program acceptability was high, delivery challenges included limited facilitator availability, a 2.5-month grant period, and outreach barriers in Black rural communities. Following the pilot field test, a sustainability plan was co-developed with community facilitators to support continued implementation and ensure that resources spent on DWDAlter were not lost.